Attitude and financial risk perceived by Facebook users in relation to a dermatology office in Lima, Peru - Bastos Perleche, Alba Agnetta (2023)
The last few years have evidenced the increasing use of social media. This has given companies the opportunity to offer their products and/or services, and has given consumers the opportunity to purchase them. The aim of this study was to determine the relationship between attitude and financial risk, as perceived by a group of users of social networking site Facebook who were interested in purchasing dermatology services. To this end, an applied study was conducted, with a quantitative, non-experimental, cross-sectional, and correlational approach. It used a five-item questionnaire which was responded by 358 users. The results indicated that 94.4% of the survey respondents stated that they had perceived a good or very good attitude from the company’s employees, generating a very low to low perceived risk in 85.5% of the survey respondents. In conclusion, a positive moderate correlation exists between attitude and financial risk.